Perlindungan Hukum Terhadap Nasabah Atas Penggunaan Bank Garansi Bersifat Unconditional Ditinjau Dari Prinsip Kehati-hatian Bank (RechtJiva, 2024)
This research is motivated by the incompleteness of the rules for using unconditional bank guarantees as collateral in government procurement projects for goods and services. This incompleteness can be seen from the absence of regulations regarding the mechanism for disbursing unconditional bank guarantee claims in Bank Indonesia Directors' Decree No. 23/88/KEP/DIR concerning Provision of Guarantees by Banks. This research uses a juridical-normative research method with a statutory approach and an analytical approach. The analysis techniques used are grammatical interpretation techniques and systematic interpretation. The research results obtained are (1) There are incomplete regulations regarding the provision of bank guarantees by banks in the Decree of the Directors of Bank Indonesia Number 23/88/KEP/DIR. Current regulations regarding the use of bank guarantees do not meet the bank's prudential principles. This can be seen from the absence of regulations regarding the process of disbursing unconditional bank guarantees, especially in conditions where there are objections from the guaranteed party. Because the disbursement process is very easy, a provision is needed that stipulates that the bank guarantee is unconditional. (2) Regulations related to bank guarantees in the Directors' Decree Number 23/88/KEP/DIR do not provide legal protection for the guaranteed against the use of unconditional bank guarantees which are currently commonly used in government goods/services procurement activities. So it is necessary to update regulations regarding the use of bank guarantees which give banks the authority to verify the veracity of bank guarantee claims and prove the truth of the default stated by the recipient of the guarantee.